La pandemia de Covid-19 y el precario desarrollo del trabajo docente en Brasil - Pessanha, Fabiana Nery de Lima; Trindade, Regina Aparecida Correia (Universidad de Costa Rica, 2022)
This essay aims to problematize, in dialogue with marxist assumptions and conceptions of dialectical historical materialism, the precariousness of teaching work in Brazil in recent decades, with emphasis on the changes caused from the Covid-19 pandemic. As a proposition, we sought a critical reflection on ideological, economic and political influences in teaching work, especially in public basic education networks. The analyses are referenced in capitalist and neoliberal offensives that plague the conditions of the teacher's work. The arguments reveal that some procedures prescribed to teachers (re)update the precariousization to the detriment of the educational and ontological principles of the work of the educators. As conclusions, we emphasize that the precariousness of teaching work is due to liberal and hegemonic projects already practiced before the pandemic and that, increasingly, they are offensive in the commodification of education and emptying of the political and ontological sense of the act of educating.